2023
DOI: 10.3390/plants12081583
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Physiological Indicators and Transcriptome Analyses Reveal the Mechanism of Selenium Multilevel Mitigation of Cadmium Damage in Brassica juncea

Abstract: Cadmium (Cd) is a common agricultural soil pollutant, which does serious harm to the environment and the human body. In this study, Brassica juncea was treated with different concentrations of CdCl2 and Na2SeO3. Then, physiological indexes and transcriptome were measured to reveal the mechanisms by which Se reduces the inhibition and toxicity of Cd in B. juncea. The results showed that Se alleviated the inhibitive Cd effects on seedling biomass, root length, and chlorophyll, and promoted the adsorption of Cd b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…According to the GO enrichment analysis, inoculation with "CD2" affected the expression of genes related to cell wall biosynthesis in roots and membranes (plasma, thylakoid, chloroplast, and photosynthetic) in aerial tissues. Similar results have been reported in Cd-stressed maize and mustard (Brassica juncea) (Peng et al, 2015;Li et al, 2023). Studies suggest that the biosynthesis of cutin, suberine, wax, and phenylpropanoid confers abiotic stress resistance in plants.…”
Section: Discussionsupporting
confidence: 81%
“…According to the GO enrichment analysis, inoculation with "CD2" affected the expression of genes related to cell wall biosynthesis in roots and membranes (plasma, thylakoid, chloroplast, and photosynthetic) in aerial tissues. Similar results have been reported in Cd-stressed maize and mustard (Brassica juncea) (Peng et al, 2015;Li et al, 2023). Studies suggest that the biosynthesis of cutin, suberine, wax, and phenylpropanoid confers abiotic stress resistance in plants.…”
Section: Discussionsupporting
confidence: 81%
“…Li's research showed that after treating B. juncea with different concentrations of Na 2 SeO 3 , the proportion of SeMet in the aboveground part was the highest, while MeSeCys and SeMet in the roots were the highest. Moreover, the increase in SeMet content in the roots effectively reduces the transportation of Cd to the aboveground part [34]. In this study, when dandelion was treated with 8 mg/L Na 2 SeO 3 , the total Se content reached 25.97 mg/kg, with organic Se accounting for 99.37%, which was of great significance for dietary Se supplementation.…”
Section: The Effect Of Se On the Nutritional Quality Of Dandelion Veg...mentioning
confidence: 54%
“…In this study, CNGC1 is a cyclic nucleotide-gated ion channel, and its high expression mediates the physiological and biochemical response of dandelion in the transport of Se to plant root cells under Na 2 SeO 3 treatment (Figure 12). In contrast to previous studies [12,34,48,50,52], the identification of these genes in dandelions treated with selenium offers valuable insights into the molecular mechanisms underlying selenium absorption and transport in crops, thus providing new supplements to the existing knowledge in this field.…”
Section: The Molecular Mechanism Of Organic Se Conversion In Dandelionmentioning
confidence: 92%